The acceptance of search-based software engineering techniques: An empirical evaluation using the technology acceptance model - Mezhuyev, Vitaliy; Al-Emran, Mostafa; Mohd Arfian, Ismail; Benedicenti, Luigi; Durkahpuvanesvari, Chandran (IEEE, 2019)
Numerous topics in software engineering can be formulated as optimization problems. Dueto the large scale of modern software systems, the methods of mathematical optimization have highcomputational complexity, and their application in many cases is not possible. To overcome this problem,search-based software engineering (SBSE) develops and applies metaheuristic search techniques to findnear-optimal solutions. Despite the significant development that the SBSE techniques (SBSET) achievedin the last years, the level of SBSET use is very low. Therefore, this paper proposes and tests a modelwhich evaluates and predicts the acceptance of SBSET by software engineering practitioners. The modelis based on the technology acceptance model (TAM) and extended by the SBSET desired properties.A total of 163 practitioners participated in the study. The perceived ease of use, perceived usefulness, andorganizational and team-based factors were all found to have significant positive effects on the actual use ofthe SBSET. This study also analyses the obstacles of SBSET acceptance and provides several proposals forits improvement in the software industry.